PROSES MORFONOLOGIS PREFIKS DALAM BAHASA WOLIO (KAJIAN TRANSFORMASI GENERATIF) - Ino, La (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2009)
This article studies the Ianguage of Wolio from the aspect of Morphology and phonology with theory of Generative Transformation. The result of analysis indicates that prefix nasal becoming original form in Language of Wolio is / N/ by alomorf / m/, / n/, /?/. Nasal / ?/ will follow obstruent consonant / k/, / g/, / i/, / e/, / a/, / o/, / u/. Nasal / n/ will follow obstruent / t/, / c/, / d/. Nasal / m/ will follow obstruent / b/, / p/. Obstruen Consonant /?/ by fitur [+ kons, + voice, + ant, + cor, + ingresif] will turn into consonant / b/ [+ kons, + voice, + ant, + cor, - ingresif] because influence of progressive assimilation of nasal by fitur [+ kons, + ant, - cor, + nas] Obstruen Consonant / D/ by fitur [+ kons, + voice, + difus] will turn into obstruen consonant / d/ by fitur [+ kons, + voice, - difus, + ant, + cor] because influence of progressive assimilation of nasal / n/ by fitur [+ kons, + son, + ant, + cor + nas]. Obstruen Consonant / s/ by fitur [+ kons, - son, + ant, + kont - high] will turn into obstruen consonant / c/ by fitur [+ kons, - voice, + ant, + high, + choir, - kont] because influence of progressive assimilation of nasal / n/ by fitur [+ kons, + sonoran, + ant. + cor, + nas].